Stakeholder attention and ambidextrous green innovation: evidence from China : research article - Cheng, Peng; Zhang, Jianye; Chen, Jiayi; Zheng, Yaoyue; Li, Zhi (Business strategy and the environment, 2025)
Based on stakeholder theory, resource dependency theory, and institutional theory, this study focuses on exploring how primary and secondary stakeholder attention differentially influences corporate green innovation. Specifically, it distinguishes between exploratory and exploitative green innovation and further analyzes how formal institutional pressures (environmental regulations, ERs) and informal institutional pressures (public environmental concern, PEC) moderate the relationship between stakeholder attention and green innovation. By analyzing empirical data from A-share listed companies in China from 2011 to 2021, the study finds that primary stakeholder attention often suppresses green innovation, while secondary stakeholder attention has a positive driving effect. Notably, the negative impact of primary stakeholder attention is mainly confined to exploitative innovation, whereas the positive influence of secondary stakeholder attention promotes both exploratory and exploitative green innovation. Moreover, the research confirms that ERs and PEC, as key factors of the institutional environment, play crucial roles in reinforcing these differential impacts. They intensify the negative effects of primary stakeholder attention on green innovation and amplify the positive impact of secondary stakeholder attention. This study enriches the field of stakeholder theory, resource dependency theory, and institutional theory, offering theoretical support and practical guidance for firms' sustainable development and green transformation.